Building a Heart-on-Chip: First Steps Towards a Vascularized Cardiac In Vitro Model - Gomez Moreno, Carolina; Paz Artigas, Laura; Santander Badules, Hazel; Ordovás Vidal, Laura; Ciriza Astrain, Jesús (Jornada de Jóvenes Investigadores del I3A, 2025)
Cancer and cardiovascular diseases are the leading causes of mortality worldwide. However, the development of new advanced treatments is limited by the lack of predictive human cardiac models. This study lays the groundwork for developing a human heart-on-chip that incorporates the interactions between the three main cardiac cell types.